Предмет: Математика,
автор: vanyashkolnik
6(x - 1) = 1 + (3x - 4)√3
Помогите пожалуйста
Ответы
Автор ответа:
2
Ответ:
6(х-1)= 1+(3х-4)√3
6х-6= 1+3(√3)х-4√3
3(√3)х- 4√3= 6х-6-1
√3(3х-4)= 6х-7 Возводим в квадрат обе части
3(3х-4)²=(6х-7)²
3(9х²-24х+16)= 36х²-84х+49
27х²-72х+48-36х²+84х-49=0
-9х²+12х-1=0
9х²-12х+1=0
D= 144-4*9*1=144-36=108
x1,2=(12+-√108)/18
x1= (12+6√3)/18
x2= (12-6√3)/18
x1=6(2+√3)/18 = (2+√3)/3
x2=(2-√3)/3
Ответ: х= (2±√3)/3
Похожие вопросы
Предмет: Русский язык,
автор: Апуся
Предмет: Русский язык,
автор: магамед10
Предмет: Английский язык,
автор: magnum2
Предмет: Экономика,
автор: Elvira505